Development of flexible microwave antennas for breast cancer imaging system - LIAQAT, Maryam (2018)
To diagnose the breast tumor, Microwave Imaging techniques are used as an alternative to X-ray Mammography. Radar-based Microwave imaging is non-ionizing , a non-invasive technique which usesback scattering rays for reconstruction of ima ges of the targeted tumor in the breast. Antennas are designed for a microwave frequency of 2GHz. Three different kinds of substrate material that are FR4, polyester and pyralux polyimide are analyzed in this project with respect to three different designs like, Rectangular Patch antenna, Bow-Tie, and Split Rectangular Patch. S-parameters, Radiation pattern and magnitude of the electric field are analyzed to determine the performance of the antenna in the air and in the presence of 3D phantom (healthy and diseased). On the bases of dielectric properties of cancerous tissues, embedded tumors are analyzed in breast phantom which is designed in HFSS. By the careful analysis of the three designs of antenna and material, a split patch antenna with pyralux polyimide substrate is the most suitable type due to compact size and efficient in performance that means high directivity and gain. Mutual coupling of the antenna is also analyzed by simulation. Two face-to-face antennas on y-axis at 72mm apart produce the best mutual coupling that is difference of S11 and S12 is -20 dB. Therefore, in array of antenna, the mutually coupled antennas are placed at 180⁰ to each other. Further, 3D breast phantom is simulated with array of two antennas using HFSS. The magnitude of electric field is 163V/m for normal breast tissues and 133.23 V/m with 10mm tumor.